2014
DOI: 10.1542/peds.2013-3828
|View full text |Cite
|
Sign up to set email alerts
|

Differential Maternal Feeding Practices, Eating Self-Regulation, and Adiposity in Young Twins

Abstract: OBJECTIVE: Restrictive feeding is associated with childhood obesity; however, this could be due to other factors that drive children to overeat and parents to restrict (eg, child genetics). Using a twin design to better control for confounders, we tested differences in restrictive feeding within families in relation to differences in twins’ self-regulatory eating and weight status. METHODS: Sixty-four same-gender twin pairs (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
61
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 51 publications
4
61
1
Order By: Relevance
“…For example, Faith et al found that for children classified as predisposed to obesity based on maternal weight, elevated child weight tended to elicit restrictive feeding practices which they argued “may exacerbate child weight control problems” (p. 435) by “disrupting the children's eating patterns” (p. 435) such as through increased eating in the absence of hunger or interference with children's self‐control over intake. Similar conclusions about the effects of restrictive or nonresponsive feeding practices are frequent . The research, however, does not yet seem to have been extended longitudinally to consider transactional processes such as whether or how disrupted eating patterns might influence parents' feeding practices over time.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Faith et al found that for children classified as predisposed to obesity based on maternal weight, elevated child weight tended to elicit restrictive feeding practices which they argued “may exacerbate child weight control problems” (p. 435) by “disrupting the children's eating patterns” (p. 435) such as through increased eating in the absence of hunger or interference with children's self‐control over intake. Similar conclusions about the effects of restrictive or nonresponsive feeding practices are frequent . The research, however, does not yet seem to have been extended longitudinally to consider transactional processes such as whether or how disrupted eating patterns might influence parents' feeding practices over time.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, instead of bidirectional processes or parent influence processes, other research points to mechanisms where parents respond to the child's weight, so that feeding practices are in response to the parent's concerns about the child's BMI or appetite, rather than BMI being influenced by feeding practices. 272,[283][284][285][286][287] Finally, there are findings of no evidence linking BMI/weight with parent feeding practices. 288,289 When authors have attempted to integrate the mixed set of findings about links between parenting and children's weight, 271 they generally fail to find systematic patterns.…”
Section: Bidirectional and Transactional Influence Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is in agreement with a recent cross-sectional study in adolescents and their mothers which also showed that mothers with very low food security were more likely to be concerned about their sons’ weight and were more likely to frequently use restrictive feeding practices with their daughters compared to food-secure mothers (Bauer et al, 2015). Restrictive feeding practices have been shown to be associated with overeating in children, such as EAH (Fisher & Birch, 2002; Liang et al, 2016; Reina et al, 2013), impaired caloric compensation (Tripicchio et al, 2014), increased energy intake (Rollins, Savage, Fisher, & Birch, 2016), and increased child weight status (Dev, McBride, Fiese, Jones, & Cho, 2013; Dinkevich et al, 2015). It remains unclear if mothers use restriction as an effort to control child’s weight or if unreliable access to food may prompt mother to ration or limit access to food to make it last longer.…”
Section: Discussionmentioning
confidence: 99%
“…These researches show that factors of family influence evaluated through the CFQ may have effects on food acceptance patterns, the development of food preferences and the self-regulation of food intake pattern by children (Tan & Holub, 2011;Tripicchio et al, 2014). Thus, the social context can intensify children's preferences for foods high in fat, sugar and salt or even foods low calorie and low nutritional value and, consequently, to develop a dislike for nutritious foods important for the health and growth in childhood, characterizing the effects of family setting on feeding children and on childhood obesity proneness or other diseases associated with poor eating habits (Faith, Carnell, & Kral, 2013).…”
Section: Discussionmentioning
confidence: 99%